1985
DOI: 10.2135/cropsci1985.0011183x002500050025x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Environment During Endosperm Cell Division in Maize: Effects on Number of Endosperm Cells and Starch Granules1

Abstract: Reductions in kernel mass are observed when corn (Zea mays L.) kernels are grown in vitro or when unfavorable temperature occurs during endosperm cell division. We investigated the possibility that a decreased number of endosperm cells or a decreased number of starch granules is responsible for the reduced kernel mass in such environments. Three‐day‐old kernels of the single cross hybrid A619 ✕ W64A were placed in culture on a denned medium at 15, 30, and 35 °C, and their growth was compared with kernels from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
2
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 0 publications
9
96
2
1
Order By: Relevance
“…However, the lower starch contents in substituted triticales suggest that the sowing temperature would probably not have been the most appropriate for their vernalization and maturation, affecting the enzymatic synthesis and accumulation of total carbohydrates and starch. High growing temperatures adversely affect starch accumulation in barley (MacLeod & Duffus, 1988), corn (Jones, Roessler, & Ouattar, 1985;Tester, South, Morrison & Ellis, 1991) and wheat (Chowdhury & Wardlaw, 1978;Liu et al, 2011;Tester et al, 1995), leading to reduction in starch accumulation and grain size. Hurkman et al (2003) observed that high temperatures during grain filling of wheat caused a decrease in starch content primarily due to the reduction in the duration of starch accumulation.…”
Section: Results and Discussion Total Carbohydrate Starch And Amylosmentioning
confidence: 99%
“…However, the lower starch contents in substituted triticales suggest that the sowing temperature would probably not have been the most appropriate for their vernalization and maturation, affecting the enzymatic synthesis and accumulation of total carbohydrates and starch. High growing temperatures adversely affect starch accumulation in barley (MacLeod & Duffus, 1988), corn (Jones, Roessler, & Ouattar, 1985;Tester, South, Morrison & Ellis, 1991) and wheat (Chowdhury & Wardlaw, 1978;Liu et al, 2011;Tester et al, 1995), leading to reduction in starch accumulation and grain size. Hurkman et al (2003) observed that high temperatures during grain filling of wheat caused a decrease in starch content primarily due to the reduction in the duration of starch accumulation.…”
Section: Results and Discussion Total Carbohydrate Starch And Amylosmentioning
confidence: 99%
“…6). In maize kernels, Jones et al (1985) reported that, starch granules per endosperm and per cell were reduced by a high temperature. Further studies are needed on the fine structural changes of translocation or accumulation system in some cereal crops.…”
Section: Abbreviations On Figuresmentioning
confidence: 99%
“…Randomly selected control kernels were transferred at 8 and 11 DAP to ABA-containing medium. Kernels were sampled from each treatment at 5, 9, and 12 d after start of culture (10,14,and 17 DAP). In study 4, the effect of ABA concentration in the medium was determined.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Both cell division and cell expansion may be important in determining the storage capacity of the kernel. Water or I temperature stress during early kernel development decreases the number of endosperm cells and starch granules (5,14,18,19) and also decreases dry matter accumulation (18,28). Since ABA accumulates in plant tissues subjected to water deficit and other types of stress, it is plausible that the effects of water deficit on kernel development may be due, in part, to elevated levels of ABA in the kernel.…”
mentioning
confidence: 99%